Body Without End: Biological Mutualism and the Body of Christ. (23rd March 2022) - Malcolm, Hannah
Abstract: This article argues that the ecological turn towards biological mutualism enlivens our understanding of the eschatological promise contained in Christ's resurrected and ascended body. I examine the implications of proposing that Christ's body was not only incarnate as microbiome, but also rose and ascended as microbiome. First, I analyse contemporary approaches to Christology's relation to creation and Andrew Davison's theological exploration of mutualism. I then respond via Irenaeus' defence of Christ's bodily resurrection and ascension as promise for all flesh. By reading Irenaeus in light of the mutualistic body, we enrich our understanding of this promise: of fruitfulness for all creation, of fullness for human nature, and that fleshly life is no ultimate barrier to union with God. Finally, I propose that this reading also offers renewed insight into the Eucharist: this promise and its implications are also made manifest at the heart of the church, Christ's body on earth.